Chlorogenic acid increased 5-hydroxymethylfurfural formation when heating fructose alone or with aspartic acid at two pH levels. (1st January 2016) - Zhang, Zhenhua; Zou, Yueyu; Wu, Taigang; Huang, Caihuan; Pei, Kehan; Zhang, Guangwen; Lin, Xiaohua; Bai, Weibin; Ou, Shiyi
Highlights: Addition of CGA increased HMF formation when heated fructose alone, or with aspartic acid. Caffeic acid is the main moiety in CGA contributing to increase HMF formation. The underlying mechanism is to enhance 3-DG formation and its conversion to HMF. Abstract: Chlorogenic acid (CGA) is a phenolic acid that ubiquitously exists in fruits. This work aims to investigate whether and how CGA influences HMF formation during heating fructose alone, or with an amino acid. The results showed that that CGA increased 5-hydroxymethylfurfural (HMF) formation. At pH 5.5 and 7.0, the addition of 5.0 μmol/ml CGA increased HMF formation by 49.4% and 25.2%, respectively when heating fructose alone, and by 9.0% and 16.7%, respectively when heating fructose with aspartic acid. CGA significantly increased HMF formation by promoting 3-deoxosone formation, and its conversion to HMF by inhibiting HMF elimination, especially in the Maillard reaction system. A comparison of the catalytic capacity of CGA with its six analogous compounds showed that both its di-hydroxyphenyl and carboxyl groups function in increasing HMF formation.